The Determinant of Online Customer Loyalty of E-Pharmacies for Herb City in Saraburi Thailand - Aeknarajindawat, Natnaporn; Aeknarajindawat, Nattachai (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
It is well known that the 21st century is an era of innovation, technological solutions, and e-commerce which has a great impact on the internet and penetration. The following study has a primary aim is to understand the positive impact of tactile information, post order convenience and E-pharmacy aesthetics on online customer loyalty through the mediating role of E-pharmacy image. The data regarding E-pharmacy and online customer loyalty has been collected from the customer service officers of the entrepreneur pharmaceutical firms. Moreover, the data mainly has been collected through a survey questionnaire and distributed among the relevant authorities. Under the distributed survey the measurement scales are also used such as purchase intention, the price premium for online purchase intention. Under the analysis section, the various analysis techniques are used such as KMO, SEM, descriptive and demographic analysis as well as factor loading, Bartlett test. A convergent validity test is also being applied to measure and examine the convergent and self-correlation of the variables. The results further illustrate that post-order convenience has an insignificant impact on online customer loyalty related to the product or use of E-pharmacy. While, the results also indicated that the E-pharmacy image has also a positive mediating role in the relationship of post-order convenience, tactile information and E-pharmacy with online customer loyalty. In the end, it is recommended that future studies must use other useful variables in another sector.